Knowledge and practices of the adolescents of the capital of Mato Grosso in relation to STD/Aids - Carleto, Amanda P.; Faria, Cleberson S.; Martins, Christine B.G.; Souza, Solange P.S.; Matos, Karla F. (Brazilian Journal of Sexually Transmitted Diseases, 2010)
Introduction: adolescence is seen as a phase of life which is marked by a series of physical and behavioral changes, which leads to certain situations of risk, among them the Sexually Transmitted Diseases (STD/aids). Objective: the study aimed at analyzing the knowledge, the perception and the occurrence in relation to STD/aids among adolescents of Cuiabá-MT. Methods: it is a descriptive, cross-sectional study, with quantitative analysis, composed by first year high school students. The data were processed by the EpiInfo with bivariate analysis (p < 0,05). Results: although the adolescents know how to name several STDs, the condom use in all intercourses was reported only by 60,0% of the boys and 29,4% of the girls. In relation to the ways of transmission of STD/aids, the index of correct answers was inferior to 20%. As a way of prevention, the use of condom and knowing the partner were mentioned. The occurrence of STD among the 13 to 15 year old boys was reported. The most frequent source of information about STD/aids are the friends, media, mother and school. Adolescents consider the high risk of acquiring STD/aids when it comes to other people, however, they consider their own risk small. Conclusion: the results point to the need for prevention against STD/aids among adolescents, with specific strategies for this clientele, so that the adolescent is not simply passive in the building of knowledge, but that can speak about himself, exchange experience and receive information in a dynamic and participative way.